Infantile Pyknocytosis: End-Tidal CO, %Micro-R Measurements, Next-Generation Sequencing, and Transfusion Avoidance with Darbepoetin - Timothy M. Bahr (Biomedicine Hub, 2020)
Infantile pyknocytosis is a rare, self-limited, hemolytic condition of unknown pathogenesis. It is diagnosed when a neonate with Coombs-negative hemolytic anemia has abundant pyknocytes and a characteristic clinical course after other hemolytic disorders has been excluded. Previous reports suggest that transfusions might be avoidable in this condition by administering recombinant erythropoietin. We cared for a patient with this disorder where we employed novel diagnostics and therapeutics. Despite these, and a good outcome free of transfusions, we continue to consider the condition to be idiopathic.